Representations of the hero character in children's theater texts - Venus Hamid Mohammed Jawad (الاكاديمي)
Children's theater is one of the arts that relies on the beautiful word and the elegant style of communicating with the child and entering his private world. It is in itself a system of moral and educational values and principles that contribute to his upbringing. Therefore, children's theater has kept pace with this development that it has witnessed in terms of its construction and has maintained its authentic Arabic character that... Uniqueness with it. The reason for choosing this topic is: because the text of children's theater is a topic that deserves study as it is a necessary foundation and basic support in that it enables the child to acquire linguistic ability, develop his mind, build his personality, entertain himself, and make him an effective member of society. Therefore, the theatrical text affects the child’s psyche if its concepts are applied in reality.